(untitled) (مجلة المنصور, 2022)
The marketing costs have great role in administrating the companies , all their marketing activities and the size of their marketing share and finally the continuity of their work and their act of competing against competitors in the markets. Those costs are considered to be the affected factors in pricing and marketing of production. The industrial organization strives to Study the needs of markets, the nature of competion of company’s productions, effecting the propes mechanism to improve the work of production lines in a way tht meet the expectations of the company. The current research intrudes an expanding of the concepts of marketing costs and their basic elements and kinds as well. Besides, the merchandising processes and its costs which represents one of the elements of marketing mix would be introduced. As far the applicatory aspect, it includes, among other things, the analysis of statements issued by the General Company of Batteries Manufacturing for research purpose in consequence of which some conclusions and recommendation that would participate in heightening interest in the elements of marketing cost would be duly drawn.